1980
DOI: 10.1002/chin.198016177
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: 3‐PHENYL‐5‐(2,2,2‐TRIFLUORO‐1‐HYDROXY‐1‐(TRIFLUOROMETHYL)ETHYL)INDOLE‐2‐CARBONITRILE, A POTENT INHIBITOR OF PROSTAGLANDIN SYNTHETASE AND OF PLATELET AGGREGATION

Abstract: Die Diazoniumverbindung (I) reagiert mit dem Ketocarbonsäureester (II) über (III) und (IV) zum Indol (V) und Pyrazolon (VI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1981
1981

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Recently, Fahrenholtz et al (23) reported findings in which a certain agent had no ulcerogenic activity but did have inhibitory effects on prostaglandin biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Fahrenholtz et al (23) reported findings in which a certain agent had no ulcerogenic activity but did have inhibitory effects on prostaglandin biosynthesis.…”
Section: Resultsmentioning
confidence: 99%